PENGARUH KOGNITIF DAN PENDAPATAN ORANG TUA PADA PRESTASI BELAJAR MAHASISWA KEPERAWATAN - Manoppo, Arlien Jeannete (Klabat Journal of Nursing, 2022)
ABSTRACT Good learning achievement is highly desired by students in their lectures, cognitive and income of students' parents have a role in their achievement. The purpose of this study was to analyze the effect of cognitive and parental income on learning achievement. Analytical observational method with cross-sectional approach was chosen in this study with 296 respondents through consecutive sampling technique. The findings of this study are that most of the students' cognitive abilities are good 159 (53.7%), the income of parents of students is in the good category 186 (62.8%), and the learning achievement shown by students is very good 147 (49.6 ). Simultaneously and partially, students' parents' cognitive and income had a significant effect (p<0.05) on academic achievement. Cognitive odds ratio value is 4.853 and parents' income is 1.678 so that the contribution of cognitive influence to learning achievement is greater than parents' income. The addition of other independent variables needs to be done to get maximum learning achievement because the influence given by the independent variable on the logistic regression model that is formed is only 19.8%. KEYWORDS: cognitive, learning achievement, parental income ABSTRAK Prestasi belajar yang baik sangat diinginkan mahasiswa dalam perkuliahannya, kognitif dan pendapatan orang tua mahasiswa memiliki peran dalam pencapaiannya. Tujuan penelitian ini adalah untuk menganalisis pengaruh kognitif dan pendapatan orang tua pada prestasi belajar. Metode observasional analitik dengan pendekatan cross-sectional dipilih dalam penelitian ini dengan 296 responden melalui teknik consecutive sampling. Temuan hasil dari penelitian ini adalah sebagian besar kognitif mahasiswa adalah baik 159 (53,7%), pendapatan orang tua mahasiswa dalam kategori baik 186 (62,8%), serta prestasi belajar yang ditunjukkan oleh mahasiswa adalah sangat baik 147 (49,6). Secara simultan dan parsial, kognitif dan pendapatan orang tua mahasiswa mempunyai pengaruh yang signifikan (p<0.05) terhadap prestasi akademik. Nilai odds ratio kognitif adalah 4,853 dan pendapatan orang tua adalah 1,678 sehingga kontribusi pengaruh kognitif terhadap prestasi belajar lebih besar dibandingkan pendapatan orang tua. Penambahan variabel independen lainnya perlu dilakukan untuk mendapatkan prestasi belajar yang maksimal karena pengaruh yang diberikan variabel independen pada model regresi logistik yang terbentuk hanya 19,8%. Kata kunci: kognitif, pendapatan orang tua, prestasi belajar